Learning Kitabah Based On The Scientific Approach with Picture Media at Islamic Junior High School - Ni Putri Asyura Impiana Asyura; Yuniar; Nazarmanto (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2025)
This research discusses the implementation of kitabah learning based on the scientific approach with picture media at Islamic Junior High School (MTs) Darussa'adah, Muara Enim. The purpose of the research is to analyze the planning, implementation, evaluation, and challenges in implementing this innovative learning model. The learning process follows five main stages, namely observing, questioning, trying, reasoning, and communicating. Picture media is used as a stimulus to increase students' imagination and vocabulary, thus supporting the development of writing skills. This type of research is descriptive qualitative. The results showed that this approach was effective in improving students' writing skills, critical thinking, and learning motivation. Evaluation was carried out by assessing aspects of attitude, knowledge and skills through formative and summative methods that also involved self-reflection and feedback from peers. Obstacles faced include limited learning resources, teacher preparation time, and the need for ongoing training. However, collaboration between teachers and adaptation of learning media are solutions to overcome these obstacles. In conclusion, the integration of the scientific approach and picture media is able to enrich Arabic language learning, especially writing skills and can be a reference for other madrasahs in developing more creative and effective learning strategies.